2015
DOI: 10.1039/c5cc05292k
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of 2,3-disubstituted indoline, pyrrolidine and cyclic ether-fused 1,2-dihydroquinoline derivatives using alkyne iminium ion cyclization of vinylogous carbamates: switch of regioselectivity using an internal hydroxy group as a nucleophile

Abstract: An intramolecular, alkyne iminium ion cyclization of vinylogous carbamates derived from o-alkynyl anilines and N-protected homopropargyl amines is developed for the stereoselective construction of trans-2,3-disubstituted indolines and pyrrolidine derivatives, respectively. The regioselectivity of the alkyne iminium ion cyclization could be switched using a hydroxy group as an internal nucleophile resulting in cyclic ether-fused 1,2-dihydroquinolines. The entire process of nitrogen heterocycle formation can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…[128] trans-2,3-Disubstituted indolines 85 were stereoselectively constructed using an intramolecular, alkyne iminium ion cyclization of vinylogous carbamates derived from orthoalkynyl anilines and N-protected homopropargyl amines (Table 4, entry 5). [129] The phenol-ene reaction proved to be effective for the direct synthesis of substituted indolines 86 using N-mesyl-1,3-diynamines as substrates (Table 4, entry 6). [130] Additional Diels-Alder route was also applied to the preparation of 4,6-substituted-N-Ac-indolines 87 using N-homopropargyl-6dichloropyrones as substrates (Table 4, entry 7).…”
Section: Transition Metal-free Synthesis Of Indolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[128] trans-2,3-Disubstituted indolines 85 were stereoselectively constructed using an intramolecular, alkyne iminium ion cyclization of vinylogous carbamates derived from orthoalkynyl anilines and N-protected homopropargyl amines (Table 4, entry 5). [129] The phenol-ene reaction proved to be effective for the direct synthesis of substituted indolines 86 using N-mesyl-1,3-diynamines as substrates (Table 4, entry 6). [130] Additional Diels-Alder route was also applied to the preparation of 4,6-substituted-N-Ac-indolines 87 using N-homopropargyl-6dichloropyrones as substrates (Table 4, entry 7).…”
Section: Transition Metal-free Synthesis Of Indolinesmentioning
confidence: 99%
“…The use of silica gel to mediate the hydroamination/semipinacol rearrangement of 2‐alkylaminophenylpropynols was described for the synthesis of 2‐oxoindolines 84 (Table 4, entry 4) [128] . trans ‐2,3‐Disubstituted indolines 85 were stereoselectively constructed using an intramolecular, alkyne iminium ion cyclization of vinylogous carbamates derived from ortho ‐alkynyl anilines and N ‐protected homopropargyl amines (Table 4, entry 5) [129] . The phenol‐ene reaction proved to be effective for the direct synthesis of substituted indolines 86 using N ‐mesyl‐1,3‐diynamines as substrates (Table 4, entry 6) [130] .…”
Section: Synthesis Of Indolinesmentioning
confidence: 99%
“…Gharpure and co-workers, while working upon alkyne-Prins type cyclization, observed that when the substrate has tethered alcohol in it 56, instead of designed indoline 57, dihydroquinoline 58 was observed as the sole product (Scheme 34). [46] The observance of later could be explained through tandem hydroalkoxylation followed by subsequent Prins type cyclization onto iminium ion, generated from vinylogous carbamate in acidic medium. Various cyclic ether fused dihydroquinolines were obtained in good yield using this cascade.…”
Section: Acid Promoted/catalyzed Intramolecular Hydroalkoxylation Cascadesmentioning
confidence: 99%
“…Later, in 2015, Gharpure and co-workers reported the stereoselective synthesis of indolines via alkyne iminium ion cyclization of enesulfonamides. 43 Tertiary enamides 139 derived from o-alkynyl anilines underwent intramolecular cyclization mediated by TMSOTf to afford indolines 140 in moderate to good yields and with good stereocontrol (Scheme 26). The authors presume that the process starts with the generation of an iminium ion 141, which is then intramolecularly trapped by the alkyne moiety, affording a cationic intermediate 142.…”
Section: Scheme 25 Stereoselective Synthesis Of Piperidinesmentioning
confidence: 99%